The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1007/s42729-021-00513-0
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping of Tea (Camellia sinensis L.) and Chinese Chestnut: Variation in the Structure of Rhizosphere Bacterial Communities

Abstract: This study was to determine the composition and diversity of soil microbial communities and evaluate the effect of intercropping on soil fertility in the tea-Chinese chestnut intercropping system. The Illumina platform was used to characterize the rhizosphere bacteria in the intercropping systems. The rhizospheric soil in intercropping systems in fall was enriched in soil organic matter, available phosphorus, and available potassium, and these were positively correlated with several bacterial taxa including Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 40 publications
4
17
0
Order By: Relevance
“…There were significant differences in the relative abundances of Myxococcota, Cyanobacteria and Verrucomicrobiota among the treatments. A previous study has demonstrated that some bacteria, such as Patescibacteria, Chloroflexi, Myxococcota and Bacteroidota, allow tea plants to obtain sufficient nutrients from the soil (Wu et al, 2021). Cyanobacteria are photosynthetic bacteria that are a fundamental component of soil biocrusts, as well as enhance soil function and structure and promote plant growth (Chua et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There were significant differences in the relative abundances of Myxococcota, Cyanobacteria and Verrucomicrobiota among the treatments. A previous study has demonstrated that some bacteria, such as Patescibacteria, Chloroflexi, Myxococcota and Bacteroidota, allow tea plants to obtain sufficient nutrients from the soil (Wu et al, 2021). Cyanobacteria are photosynthetic bacteria that are a fundamental component of soil biocrusts, as well as enhance soil function and structure and promote plant growth (Chua et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with monoculture, intercropping improves soil fertility and plant diversity, reduces weeds, and improves light interception and utilization [ 8 , 9 ]. Tea plants are perennial shrubs, and intercropping with other plants such as chestnut and legumes has been developed in a wide range of forms and applied in different tea gardens [ 10 , 11 ]. In some intercropping systems, intercropped plants may compete for soil N, and the yield and/or tea quality may be adversely affected.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some other protective factors, such as allantoic acid, sugars, and unsaturated fatty acids, were higher in Chinese chestnut intercropped tea than mono-cropped tea [ 1 ]. Meanwhile, the soil nutrients, including nitrogen, phosphorus, potassium, and organic matter, were increased in the Chinese chestnut-tea intercropping field, and some beneficial bacteria were enriched in the intercropped soil [ 2 ]. In the rubber intercropped tea garden, the land expectation value was significantly higher than that in rubber or tea mono-cropped gardens, and the prices for rubber and tea were also improved [ 3 ].…”
Section: Introductionmentioning
confidence: 99%